Relationship between TLR4 signalling alterations and effective human cytomegalovirus infection - Germini, D.; Arcangeletti, M.C. (Вiopolymers and Cell, 2014)
Toll-like receptors (TLR), the main class of immune-sensor molecules triggering the innate immunity pathways, are known to be involved in the infection of different RNA and DNA viruses, including herpesviruses. Human cytomegalovirus (HCMV) is a widespread human beta-herpesvirus that infects 80–90 % of the world’s population and it can cause severe and even fatal diseases in immunocompromised patients and it is also responsible for birth defects as a consequence of congenital infection. Aim of this review is to discuss the existing data regarding the role of TLRs in HCMV concentrating mainly on TLR4. A better understanding in this relationship could be exploited for the development of efficient early diagnosis methodologies and anti viral therapies. Toll-подібні рецептори (TLR) як основний клас молекул імунних датчиків, що регулюють сигнальні шляхи вродженого імунітету, також беруть участь у зараженні різними РНК- і ДНК-вірусами, з-поміж яких віруси герпесу. Цитомегаловірус людини – широко розповсюджений бета-герпесвірус людини, їм заражаено приблизно 80–90 % населення земної кулі, що призводить до серйозних і навіть смертельних захворювань у пацієнтів з імунодефіцитом та є причиною спадкових патологій через вроджені інфекції. Мета цього огляду полягає в обговоренні існуючих даних щодо ролі TLR, і особливо TLR4, в цитомегаловірусній інфекції. Краще розуміння цього може бути використано для розробки ефективних методик ранньої діагностики і противірусних препаратів. Toll-подобные рецепторы (TLR) как основной класс молекул иммунных датчиков, регулирующих сигнальные пути врожденного иммунитета, участвуют также в заражении различными РНК- и ДНК-вирусами, включая вирусы герпеса. Цитомегаловирус человека – широко распространенный бета-герпесвирус человека, им заражаено примерно 80–90 % населения земного шара, что приводит к серьезным и даже смертельным заболеваниям у пациентов с иммунодефицитом и является причиной наследственных патологий из-за врожденной инфекции. Цель представленного обзора состоит в обсуждении существующих данных о роли TLR, и особенно TLR4, в цитомегаловирусной инфекции. Лучшее понимание этого может быть использовано для разработки эффективных методик ранней диагностики и противовирусных препаратов.